The law of contracts - McCamus, John D. (Irwin Law, 2020)
"The Law of Contracts, third edition, is a thorough revision of this authoritative text in Irwin Law's Essentials of Canadian Law series. It includes discussion of recent jurisprudential developments in a variety of topics including: The impact of the ground-breaking decision in Bhasin v Hrynew, 2014 SCC 71, in articulating the general organizing principle requiring good faith performance underlying the existing law imposing duties of good faith contractual performance and the recognition of a new good faith duty of honest performance The potential implications of Bhasin v Hrynew for the duty to bargain in good faith The effect of the decision of the Supreme Court of Canada in Canada (Attorney General) v Fairmont Hotels Inc, 2016 SCC 56, on the law of rectification for mistake The continuing development of the Canadian jurisprudence applying the Tercon rule to the enforceability of exculpatory clauses The impact of Uber Technologies Inc v Heller, 2020 SCC 16 and Douez v Facebook Inc, 2017 SCC 33, on the doctrine of unconscionability The potential impact of Southcott Estates Inc v Toronto District Catholic School Board, 2012 SCC 51, on the law of mitigation and of specific performance The effect of Globe Motors Inc v TRW Lucas Varity Electronic Steering Ltd (Eng CA) on the enforceability of "no oral variation" clauses The book also incorporates reference to recent Canadian cases on doctrines such as estoppel, privity, interpretation and appellate review, and discussion of recent leading authorities dealing with such matters as contractual interpretation and the application of the basic principles of formation to e-commerce. The Law of Contracts is an indispensible resource for anyone interested in modern Canadian contract law."–Publisher's description
QID: Q136026991